Entrepreneurship Empowered by Artificial Intelligence - Janković, Nikola; Lečić-Cvetković, Danica; Rajković, Teodora (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Artificial Intelligence (AI) is changing entrepreneurship by transforming how companies innovate, operate and stay competitive in the digital era. This paper examines how AI is becoming part of entrepreneurial practices and its impact on improving operations. This research combines theoretical frameworks with practical examples to outline best practices for AI adoption among entrepreneurs. The purpose of this study is to examine how AI contributes to driving innovation, improving operational efficiency and increasing customer engagement. The aim of this paper is to provide actionable insights into leveraging AI for competitive advantage. The intention of this paper is to inspire entrepreneurs to adopt responsible and strategic approaches to AI integration. By synthesizing theoretical insights and practical findings, this paper underscores the transformative potential of AI, guiding entrepreneurs toward growth and progress in the digital economy.